2000
DOI: 10.1111/j.1751-908x.2000.tb00777.x
|View full text |Cite
|
Sign up to set email alerts
|

CO2‐Laser Extraction‐Static Mass Spectrometry Analysis of Ultra‐Low Concentrations of Nitrogen in Silicates

Abstract: A new installation for the analysis of picomole quantities of nitrogen has been designed and constructed. It permits the simultaneous analysis of N and rare gases extracted from silicates by heating. The extraction procedure involves the use of a CO2 laser as a heater, and the analysis is made by static mass spectrometry using a high sensitivity, high resolution mass spectrometer. Procedural blanks of 2 picomoles N2 (60 picogram N) allow us to analyse routinely N in mg‐sized samples such as mantle‐derived and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 10 publications
2
17
0
Order By: Relevance
“…A second extraction step on fragment 4 released ≤1% of the total amounts of its noble gas contents (Table , , and ), in agreement with the fact that more than 99% of noble gases are extracted by CO 2 infrared laser heating when a spherule of molten silicate is obtained (Humbert et al. ).…”
Section: Resultssupporting
confidence: 70%
See 2 more Smart Citations
“…A second extraction step on fragment 4 released ≤1% of the total amounts of its noble gas contents (Table , , and ), in agreement with the fact that more than 99% of noble gases are extracted by CO 2 infrared laser heating when a spherule of molten silicate is obtained (Humbert et al. ).…”
Section: Resultssupporting
confidence: 70%
“…The formation of a spherule of molten silicate indicated that the melting temperature of the sample had been reached, and that more than 99% of the gas had been extracted (Humbert et al. ). A re‐extraction was carried out on fragment 4, with negligible amounts of gas being released, in line with a complete extraction of the gas upon initial melting.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After leaving the samples under high vacuum (P ≤ 10 -8 Torr) for one week prior to analysis, they were heated individually with a continuous mode infrared CO 2 laser (λ = 10.6 μm). While three samples (#6, 10, 11) were heated to melting in a single step, two temperature steps (~600°C and fusion) were applied to all other samples by modulating the power of the laser and monitoring the heating procedure on a TV screen using a CCD camera (Humbert et al, 2000) (Fig. 2).…”
Section: Noble Gas and Nitrogen Analysismentioning
confidence: 99%
“…Noble gas (Ne and Ar) and nitrogen abundances and isotope ratios were determined by CO 2 laser extraction-static mass spectrometry (Humbert et al, 2000;Hashizume and Marty, 2004). The twelve CAI and two matrix fragments were loaded into different pits of the laser chamber connected to the purification line of the Micromass VG5400 mass spectrometer at the CRPG noble gas analytical facility.…”
Section: Noble Gas and Nitrogen Analysismentioning
confidence: 99%